Enkephalin-δ opioid receptor signaling partly mediates suppression of LH release during early lactation in rats - Hitomi TSUCHIDA; Marina TAKIZAWA; Miku NONOGAKI; Naoko INOUE; Yoshihisa UENOYAMA; Hiroko TSUKAMURA (The Society for Reproduction and Development, 2023)
Gonadal function is often suppressed during lactation in mammals including rodents, ruminants, and primates. This suppression is thought to be mostly due to the inhibition of the tonic (pulsatile) release of gonadotropin-releasing hormone (GnRH) and consequent gonadotropin. Accumulating evidence suggests that kisspeptin neurons in the arcuate nucleus (ARC) play a critical role in the regulation of pulsatile GnRH/gonadotropin release, and kisspeptin mRNA (Kiss1) and/or kisspeptin expression in the ARC are strongly suppressed by the suckling stimuli in lactating rats. This study aimed to examine whether the central enkephalin-δ-opioid receptor (DOR) signaling mediates the suckling-induced suppression of luteinizing hormone (LH) release in lactating rats. Central administration of a selective DOR antagonist increased the mean plasma LH levels and baseline of LH pulses in ovariectomized lactating mother rats compared to vehicle-injected control dams on day 8 of lactation without affecting the number of Kiss1-expressing cells and the intensity of Kiss1 mRNA signals in the ARC. Furthermore, the suckling stimuli significantly increased the number of enkephalin mRNA (Penk)-expressing cells and the intensity of Penk mRNA signals in the ARC compared to non-lactating control rats. Collectively, these results suggest that central DOR signaling, at least in part, mediates the suppression of LH release induced by suckling stimuli in lactating rats via indirect and/or direct inhibition of ARC kisspeptin neurons.